Çalışma koşullarında değişiklik ve iş sözleşmesinin feshi - Özgül, Merve (My University, 2010)
İş güvencesinin hukukumuza girmesi ile birlikte işçinin işinin korunması ve feshin son care olarak uygulanması gerektiği konuları da ön plana çıkmıştır. Feshin son çare olması ilkesi, iş güvencesi sisteminin temelinde yatan sözleşmeye bağlılığın esas feshinse istisna olduğu yönündeki düşüncenin bir sonucu olarak hukukumuzda da yerini almıştır. Feshin son çare olması gerektği ilkesinin ele alndığı düzenlemelerden birisi de 4857 sayılı İş Kanununun 22.maddesidir. ‘Çalışma Koşullarında Değişiklik ve İş Sözleşmesinin Feshi’ başlığı altındaki bu düzenleme ile işveren iş akdinin kaçınılmaz olduğu hallerde iş akdinin feshinden daha az işçiye zarar verecek bir düzenlemeyi işçinin yazılı olarak kabul etmesi şartıyla uygulayabilmekte bu değişikliği kabul eden işçi de işini kaybetme riskinden kurtulmaktadır. İş K.m.22’nin 1475 sayılı İş Kanunu dönemindeki işçi aleyhine olan bir çok uygulamayı ortadan kaldırdığını, işletme riskini işçi üzerinden alarak işverene bıraktığını söylemek mümkünse de çalışma koşullarında değişikliğin iş sözleşmesinin feshi kavramından ayrı olarak ele alınmış olması İş K.m.22’de getirilen düzenlemenin tam anlamıyla değişiklik feshi niteliği taşımadığını düşündürmektedir.

The issues stating that the protection of the worker and termination should be implemented as the ultimate remedy became prominent with the inclusion of job security in our law. The ultimate remedy principle for termination came into our law as a result of the fact that the adherence is the basis for the contract, on which the job security system is based, while the termination is only an exception. Article 22 of Labour Law numbered 4857 is one of the regulations, in which the principle that the termination should be the ultimate remedy is discussed. Through this regulation under the title Amendments in Working Conditions and Termination of the Labour Contract, the employer can implement a regulation, which harms the worker less than the termination of the labour contract in cases where the labour contract is inevitable, provided that the worker accepts it in written form while the worker, who accepts this amendment, is kept clear of losing his/ her job. Even though it is possible to say that the Labour Law article 22 abolished many implementations, which were against the worker during the term of the Labour Law numbered 1475, and that it took the enterprise risk from the shoulders of the worker and left it to the employer; the fact that the issue of amendment in the working conditions are considered separately from the termination of the labour contract makes us think that the regulation implemented in Labour Law article 22 does not have the quality of amendment termination completely.
Keywords: Fesih; İş Hukuku; İş Sözleşmeleri; İşçi; Sosyal Güvenlik